Analisis Kemampuan Berhitung Siswa Kelas III SD Negeri Kecamatan Ulaweng Kabupaten Bone - Syamsuddin S; Muhammad Idris Jafar; Rahmawati Patta (Publikasi Pendidikan, 2018)
This research aims to acquaire the description of ability level elementary students third grade at district Ulaweng, regency of Bone. The population is the entire elementary students third grade at district Ulaweng, regency of Bone. Samples are drawn by random in every group supervision UPTD grade at district Ulaweng, regency of Bone.Since there are four group supervision, those four schools become samples in which elementary students third grade are the subject of research.Instrument of data collection uses test. Data of test result is then analysed by descriptive statistical technique in the form of distribution of frequency, aritmetic mean, standard deviation, and percentage.Based on analysis data, it is summarizedthat the levelofcalculatingabilityelementary students third grade at district Ulaweng, regency of Bone is considered low. It is then recommended to all stakeholders in academic field to make serious effort to enhance math learning process at elementary school.